Transvase: quando a ficção invade a realidade - Chinita, Fátima (2013)
ABSTRACT: Adopting the concept of metalepsis, as explained by Gérard Genette, I intend to tackle the miscegenation of ontological worlds as practiced in metacinematic films dealing either with the creator or the spectator and made famous with Woody Allen’s film The Purple Rose of Cairo (1985, EUA). Assuming the existence of two adjoining fictional universes, one of them intrafilmically projected onto a screen and the other positioned in front of it so as to create or observe the other, one realizes that, in fact, they both communicate in a more intense way. That is, they both can cross the barrier that separates them and function, literally, as communicating vessels thrusting themselves onto the other side of fiction. The use of this screen passage technique – which I call ‘spilling narrative’ – although it takes place inside the film, at an intradiegetic level, cannot be considered a simple comic effect. In actuality, it is a very serious affair, denoting the authorial intervention as a reflexive practice of écriture by means of a mise en abyme, according to Lucien Dällenbach. Therefore, the fictional spilling over of worlds which totally blends together both sides of the twice artificial universe of the fabula, represents the emotional and intellectual involvement of the creator with his/her creation and of the spectator with the world watched. Both illustrate the desire of fusion inherent in the acts of creation and reception. My approach will be based on Gabriele Salvatores’ Happy Family (2010) and Wojciech Marczewski’s Escape from the ‘Liberty’ Cinema (1990).